Power systems automation, communication, and information technologies for smart grid: A technical aspects review - Vikram Kulkarni; Sarat Kumar Sahoo; Sudhakar Babu Thanikanti; Srikanth Velpula; Dharmesh Ishwerlal Rathod (Universitas Ahmad Dahlan, 2021)
Smart grid (SG) introduced proven power system, based on modernized power delivery system with introduction of advanced data-information and communication technologies (ICT). SGs include improved quality of power transmission/distribution from power generation to end-users with optimized power flow and efficiency. In addition to above modern automation, two-way communications, advanced monitoring, and control to optimize power quality issues are the classic features of SGs. This ensures the efficiency and reliability of all its interconnected power system elements against potential threats and life time cycle. By integrating ICT into the power system SGs improved the working capabilities of the utility companies. Resultant of ICT with SG leads to better management of assets and ensure energy management for end users. This review article presents the different areas of communication and information technology areas involved in SG automation.